Non-Melanoma Skin Cancer and Vitamin D: The “Lost Sunlight” Paradox and the Oxidative Stress Explanation - Emmanouil Karampinis; Athina-Maria Aloizou; Efterpi Zafiriou; Alexandra Bargiota; Zoi Skaperda; Demetrios Kouretas; Angeliki-Viktoria Roussaki-Schulze (Antioxidants, 2023)
UV radiation (UVR) is responsible for inducing both harmful and beneficial effects on skin health. Specifically, it has been reported to disrupt oxidant and antioxidant levels, leading to oxidative stress conditions in skin tissue. This phenomenon might trigger photo-carcinogenesis, resulting in melanoma, NMSC (non-melanoma skin cancer), such as BCC (basal cell carcinoma) and SCC (squamous cell carcinoma), and actinic keratosis. On the other hand, UVR is essential for the production of adequate vitamin D levels, a hormone with important antioxidant, anticancer and immunomodulatory properties. The exact mechanisms implicated in this two-fold action are not well understood, as there still no clear relation established between skin cancer and vitamin D status. Oxidative stress seems to be a neglected aspect of this complex relation, despite its role in both skin cancer development and vitamin D deficiency. Therefore, the aim of the present study is to examine the correlation between vitamin D and oxidative stress in skin cancer patients. A total of 100 subjects (25 with SCC, 26 with BCC, 23 with actinic keratosis, and 27 controls) were assessed in terms of 25-hydroxyvitamin D (25(OH) D) and redox markers such as thiobarbituric acid reactive substances (TBARS), protein carbonyls, total antioxidant capacity (TAC) in plasma, glutathione (GSH) levels and catalase activity in erythrocytes. The majority of our patients revealed low vitamin D levels; 37% of the subjects showed deficiency (<20 ng/mL) and 35% insufficiency (21–29 ng/mL). The mean 25(OH) D level of the NMSC patients (20.87 ng/mL) was also found to be significantly lower (p = 0.004) than that of the non-cancer patients (28.14 ng/mL). Furthermore, higher vitamin D levels were also correlated with lower oxidative stress (positive correlation with GSH, catalase activity TAC index and negative correlation with TBARS and CARBS indices). NMSC patients diagnosed with SCC showed lower catalase activity values compared to non-cancer patients (p < 0.001), with the lowest values occurring in patients with a chronic cancer diagnosis (p < 0.001) and vitamin D deficiency (p < 0.001). Higher GSH levels (p = 0.001) and lower TBARS levels (p = 0.016) were found in the control group compared to the NMSC group, and to patients with actinic keratosis. Higher levels of CARBS were observed in patients with SCC (p < 0.001). Non-cancer patients with vitamin D sufficiency showed higher TAC values compared to non-cancer patients with vitamin D deficiency (p = 0.023) and to NMSC patients (p = 0.036). The above-mentioned results indicate that NMSC patients reveal increased levels of oxidative damage markers compared to control levels, while vitamin D status plays a critical role in the determination of individuals’ oxidative status.